Estimation Of The Thermochemical And Solubility Properties Of Some Nigerian Softwood - Ejikeme Chigozie, M.; Ezeonu Chukwuma, S.; Eboatu Augustine , N. (Journal of Environmental Science and Engineering Technology, 2016)
The abundance of softwoods in Nigeria makes them readily available and their renewability is also an advantage in generation of any product that has usefulness in scientific application. All the softwood samples investigated were soluble in hot concentrated H2SO4. From a measured quantity of each Nigerian softwood powder consumed in their destructive distillation, the results showed that: Tetrapleura tetraptera had appreciable quantities of wood charcoal with a maximum value of 5.2g, Allanblackia floribunda, Afzelia bella and Afrormosia laxiflora each with 4.5g also had high quantities of wood charcoal. Afzelia bipindensis, Cassipourea barteri and Khaya ivorensis each produced 3.00cm3 pyroligneous acid volume. Tar volumes of 0.25cm3 as the highest value was observed in each of Monodara tenuifolia, Anogeissus leiocarpus, Amphimas pterocarpoides, Afzelia bipindensis and Cassipourea barteri. The volumes of wood gas emitted were high. The maximum wood gas emitted showed values of 998 and 980cm3 from Afzelia bipindensis and Sacoglottis gabonensis. These thermochemicals have agricultural, industrial and domestic values.